Strategy for Improving Library Facilities and Infrastructure in The Development of Modern Library in Pandemic Era - Murliasari, Rikha (Indonesian Journal of Librarianship, 2021)
Background: Worried that it will impact the spread of the corona virus transmission, many library services in several regions in Indonesia have closed their services without first analyzing the strengths, weaknesses, opportunities and threats of libraries in the midst of the Covid 19 pandemic. Purpose: The purpose to find out how the strategies used to improve library facilities and infrastructure in the development of modern libraries during the pandemic. Methods: This research uses library research. In making policies related to the scenario of library service strategies in the midst of the Covid 19 pandemic, an analysis was carried out using a SWOT analysis tool, so that the policies determined would be more targeted. Result: The development of facilities and infrastructure needs to be carried out in the pandemic era. Improving digital library supporting facilities is a top priority in addition to physical facilities. Based on the SWOT analysis, it was found that policy suggestions/programs for improving infrastructure include procurement/improvement of digital library systems, procurement/improvement of servers as storage databases, improvement of digital/electronic collections, procurement/improvement of automation facilities and digital media transfer, and the need for structuring and improving facilities. and attractive and contemporary library physical infrastructure without violating health protocols.. Conclusion: The strategy for developing facilities and infrastructure in the context of developing modern libraries during the pandemic leads to increasing digital library support facilities which include procurement/improvement of digital library systems, procurement/improvement of servers as storage databases, increasing digital/electronic collections, automation and digital media transfer. Keywords: Facilities and infrastructure; Modern Libraries; Pandemic